Respuesta :
Answer:
x²+4x−12
Step-by-step explanation:
=(x+−2)(x+6)
=(x)(x)+(x)(6)+(−2)(x)+(−2)(6)
=x²+6x−2x−12
=x²+4x−12
- You multiply the first x and the first x in the second bracket
= x²
- You multiply the first x and the last number in the second bracket (6)
= 6x
-You multiply -2 and the first number of the second bracket x
= -2x
- You multiply both the last numbers in both of the brackets
= -2 x 6
= -12
then write it all out
=x²+6x−2x−12
=x²+ ( you have like terms so add them) -12
=x²+4x−12